1998
DOI: 10.1016/s0375-9601(98)00169-8
|View full text |Cite
|
Sign up to set email alerts
|

The causal interpretation of dust and radiation fluid non-singular quantum cosmologies

Abstract: We apply the causal interpretation of quantum mechanics to homogeneous and isotropic quantum cosmology where the sources of the gravitational field are either dust or radiation perfect fluids. We find non-singular quantum trajectories which tends to the classical one when the scale factor becomes much larger then the Planck length. In this situation, the quantum potential becomes negligible. There are no particle horizons. As radiation is a good approximation for the matter content of the early universe, this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 9 publications
3
143
0
3
Order By: Relevance
“…A proposal to circumvent this problem consists of assuming a trajectory formulation of quantum mechanics [114,115] in which the scale factor follows specific trajectory values [116]. Applying this formalism and assuming regular boundary conditions, one finds that all possible trajectories are nonsingular and include a bounce [117] (see also [118] for a different but related approach). Of course, all known formulations of quantum mechanics being strictly equivalent, the fact that the universe underwent a regular bouncing phase or not should not depend on which formulation one picks, so it is reasonable to expect that the results obtained in Refs.…”
Section: Canonical Quantum Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…A proposal to circumvent this problem consists of assuming a trajectory formulation of quantum mechanics [114,115] in which the scale factor follows specific trajectory values [116]. Applying this formalism and assuming regular boundary conditions, one finds that all possible trajectories are nonsingular and include a bounce [117] (see also [118] for a different but related approach). Of course, all known formulations of quantum mechanics being strictly equivalent, the fact that the universe underwent a regular bouncing phase or not should not depend on which formulation one picks, so it is reasonable to expect that the results obtained in Refs.…”
Section: Canonical Quantum Cosmologymentioning
confidence: 99%
“…Such an approach is usually unfeasible unless an additional mini-superspace approximation is performed, in which the infinite number of degrees of freedom is reduced to a few, for instance by considering only homogeneous and isotropic metrics. In [117], it was shown that in the presence of a simple perfect fluid, the singularity can always be avoided, independent of the fluid's equation of state and the spatial curvature. Moreover, perturbations in such models can be treated self-consistently.…”
Section: Modified Gravitymentioning
confidence: 99%
“…Bouncing cosmological models, [1][2][3][4][5][6] which solve the singularity problem, can also be considered as possible alternatives to inflation, as long as they are able to solve the horizon and flatness problems, and justify the observed power spectrum of primordial cosmological perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…A bouncing phase may originate from quantum gravity [7] or quantum cosmology [8], and have been seen to occur in some string-motivated models [9]. In one such model, based on the brane hypothesis in a five dimensional context, namely the ekpyrotic scenario [10], [11], the bounce in fact does not address the singularity problem since it is assumed to be singular.…”
Section: Introductionmentioning
confidence: 99%